The Kwyjibo Polymetallic Iron Oxide Deposit, Northeastern Grenville Province, Quebec - Francis Chartrand (Canadian Institute of Mining, Metallurgy and Petroleum, 2003)
The Kwyjibo deposit is an iron oxide Cu-REE-F-Mo-Au mineralization of Mesoproterozoic age located in the Grenville Province approximately 120 km NE of Sept-Îles, Quebec (Figure 1). Occurring along the SE margin of the Canatiche granitic complex, the deposit is composed of several polymetallic showings that are related to different textural facies of magnetite. The mineralization process at Kwyjibo is complex, and is divided into Early Granitophile, Magnetite, Main Polymetallic and Specular Hematite stages (Cayer et al., submitted for publication). The Main Polymetallic stage, comprising chalcopyrite, pyrite, fluorite, molybdenite and REE-bearing minerals, is superimposed on pre-existing magnetiterich rocks. Discovered by SOQUEM Inc. in 1993, the Kwyjibo deposit shares many characteristics with other hydrothermal polymetallic iron oxide deposits around the world. Foose and McLelland (1995) suggested that this class of mineralization could occur in the Grenville Province. However, only a few polymetallic occurrences are known to be associated with low-Ti iron oxide deposits in the Grenville. Kwyjibo is one of the most significant examples of a polymetallic iron oxide deposit to have been found in the Grenville Province to-date.